Transcriptional and Molecular Pathways Activated in Mesenteric Adipose Tissue and Intestinal Mucosa of Crohn's Disease Patients - Andressa Coope; Lívia Bitencourt Pascoal; Francesca Aparecida Ramos da Silva; José Diego Botezelli; Maria de Lourdes Setsuko Ayrizono; Marciane Milanski; Michel Gardere Camargo; Núria Planell; Mariana Portovedo; Cilene Bicca Dias; João José Fagundes; Raquel Franco Leal (Hindawi Limited, 2017)
Crohn's disease (CD) is a chronic inflammatory disorder, characterized by cytokine imbalance and transcription signaling pathways activation. In addition, the increase of mesenteric adipose tissue (MAT) near the affected intestinal area is a hallmark of CD. Therefore, we evaluated the transcription signaling pathways and cytokines expression in intestinal mucosa and MAT of active CD patients. Ten patients with ileocecal CD and eight with noninflammatory diseases were studied. The biopsies of intestinal mucosa and MAT were snap-frozen and protein expression was determined by immunoblotting. RNA levels were measured by qPCR. The pIkB/IkB ratio and TNFα level were significantly higher in intestinal mucosa of CD when compared to controls. However, STAT1 expression was similar between intestinal mucosa of CD and controls. Considering the MAT, the pIkB/IkB ratio was significantly lower and the anti-inflammatory cytokine IL10 was significantly higher in CD when compared to controls. Finally, the protein content of pSTAT1 was higher in MAT of CD compared to controls. These findings reinforce the predominance of the proinflammatory NF-kB pathway in CD intestinal mucosa. For the first time, we showed the activation of STAT1 pathway in MAT of CD patients, which may help to understand the physiopathology of this immune mediated disease.